TINGKAT STRES DAN BURNOUT FAMILY CAREGIVER LANSIA - Duma Lumban Tobing; Indira Cahyani (Jurnal Keperawatan Widya Gantari Indonesia, 2026)
Family caregivers who care for older people often face long-term physical, psychological, social, and economic pressures. This condition can increase stress levels and potentially trigger burnout. This study aims to analyze the relationship between stress levels and burnout in elderly family caregivers. The study used a correlational design with a cross-sectional approach and stratified random sampling. A total of 222 elderly family caregivers in Village X, Bogor City, were involved as respondents. Stress levels were measured using the Kingston Caregiver Stress Scale, while burnout was measured using the Maslach Burnout Inventory. Data analysis was performed univariately using descriptive statistics and bivariately using the chi-square test. The results showed that family caregivers had an average age of 39.24 years, the majority were female (75.2%), had a high school education (34.2%), were married (65.8%), had no income (43.7%), and had been in the caregiving role for more than five years (55.0%). The chi-square test showed a significant association between stress levels and burnout incidence among elderly family caregivers (p = 0.001). These findings suggest the need for family-based nursing interventions in the community that focus on early detection of stress and on strengthening coping strategies to prevent burnout among elderly family caregivers.